A business-cycle model with money-in-utility (MIU) and government sector: the case of Bulgaria (1999-2020) - Aleksandar Vasilev (Journal of Economic and Administrative Sciences, 2022)
Purpose: We augment an otherwise standard business cycle model with a richer government sector, and add money-in-utility (MIU) considerations to study economic fluctuations. Design/methodology/approach: More specifically, real money balances enter in a non-separable way with consumption and leisure. This specification is then calibrated to Bulgarian data after the introduction of the currency board (1999-2020), gives a role to money in accentuating economic fluctuations. Findings: This novel mechanism allows the framework to reproduce - better than the RBC model - the observed variability and correlations among model variables, and those characterizing the labor market in particular. In addition, money is non-neutral and affects aggregate economic activity. Originality: This is the first micro-founded monetary-DSGE model on Bulgaria trying to explain the role of money for economic fluctuations.
Keywords: E32; 330; business cycles; money-in-utility (MIU) considerations